Flying dinosaurs : how fearsome reptiles became birds - Pickrell, John (NewSouth Publishing, 2014)
Dinosaurs didn't die out when an asteroid hit Earth 66 million years ago. Get ready to unthink what you thought you knew and journey into the deep, dark depths of the Jurassic. The discovery of the first feathered dinosaur in China in 1996 sent shockwaves through the palaeontological world. Were the feathers part of a complex mating ritual, or a stepping stone in the evolution of flight? And just how closely related is T. rex to a chicken? Award-winning journalist John Pickrell reveals how dinosaurs developed flight and became the birds in our backyards. He delves into the latest discoveries in.